2020
DOI: 10.1590/1981-22562020023.200069
|View full text |Cite
|
Sign up to set email alerts
|

Fatores associados à condição de acamado em idosos brasileiros: resultado da Pesquisa Nacional de Saúde, 2013

Abstract: Resumo Objetivo Identificar os fatores associados à condição de acamado entre idosos brasileiros, analisando-se condições socioeconômicas e de saúde e utilização de serviços de saúde. Método Estudo transversal com dados secundários provenientes da Pesquisa Nacional de Saúde (2013). Contou com a população de indivíduos com ≥60 anos (n=11.177). A condição de acamado foi considerada variável dependente e as características sociodemográficas, condições de saúde e utilização de serviços médicos como independentes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 26 publications
0
4
0
4
Order By: Relevance
“…This pattern seems to be different from what occurs with medical consultations. A study conducted in Brazil indicated that bedridden older adults had 4 or more medical appointments in the year prior to the survey 6 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This pattern seems to be different from what occurs with medical consultations. A study conducted in Brazil indicated that bedridden older adults had 4 or more medical appointments in the year prior to the survey 6 .…”
Section: Discussionmentioning
confidence: 99%
“…The sample size calculation was based on the 2010 Census data, which counted 48423 people over 60 years old in the municipality. Of these, an estimated proportion of 4.9% were bedridden 6 . Considering a homogeneous sample, a sampling error of 5% and a confidence level of 95%, we reached the number of 223 people.…”
Section: Sampling Planmentioning
confidence: 99%
See 2 more Smart Citations
“…O cálculo amostral foi realizado com base nos dados do Censo de 2010, que contabilizou 48.423 pessoas com mais de 60 anos no município. Destes, aplicou-se a estimativa de uma proporção de 4,9% de acamados 6 . Considerando uma amostra homogênea, um erro amostral de 5% e um nível de confiança de 95%, chegou-se ao número de 223 pessoas.…”
Section: Plano Amostralunclassified